ECENT ADVANCES IN KNOWLEDGE OF SOIL-TRANSMITTED HELMINTHS - Paul C. Beaver (Tehran University of Medical Sciences, 1975)
New observations in recent years have accented differences between the two common hookworms, Ancylostoma duodenale and Necator americanus,"nwith respect to modes of transmision and pathogenicity, and have established Ancylostoma ceylanicum as a species distinct from A. braziliense. Transmammary and paratenic transmission are now considered to be natural modes of infection in Ancylostoma caninum and possibly 111 other Ancylostoma species including A. duodenale, but not in Necator. The question of relative blood losses from laceration hemorrhage and blood-sucking in hookworm anemia is unresolved. The prevalence of Loeffler's syndrome in pulmonary ascariasis appears to be greatest in areas where transmission is sharply seasonal. Recent studies have failed to confirm reports of blood-sucking by Trichuris. Milk-borne transmission from mother to the newborn has been demonstrated for numberous species of Strongyloides not including S. stercoralis. Zoonotic soil-transmitted helminths 0; dogs and cats have become recognized as frequently causing visceral larva migrans and occasionally blindness in most parts of the world. Two major advances were made in diagnostic techniques - the Harada-Mori test-tube hookworm culture for species diagnosis and the Kato cellophane-covered thick fecal film ror ranid and quantitative diagnosis of intestinal helminth infections.